Science on the air : popularizers and personalities on radio and early television - La Follette, Marcel Chotkowski, 1944- (University of Chicago Press, 2008)
Mr. Wizard's World. Bill Nye the Science Guy. NPR's Science Friday. These popular television and radio programs broadcast science into the homes of millions of viewers and listeners. But these modern series owe much of their success to the pioneering efforts of early-twentieth-century science shows like Adventures in Science and "Our Friend the Atom." Science on the Air is the fascinating history of the evolution of popular science in the first decades of the broadcasting era. Marcel Chotkowski LaFollette transports readers to the early days of radio, when the new medium allowed innovativ.